Education, politics and culture andina - Vargas Salgado, Humberto (2013)
Discusses the problems of education, politics and culture in the Peru current, stressing issues such as reforms of education, multiculturalism, and intercultural intraculturality, ethnicity and indigenous rights and democracy and contemporary politics in our country